2004
DOI: 10.1248/bpb.27.1864
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Small Rat Hepatocytes Express both Annexin III and Terminal Differentiated Hepatocyte Markers, Tyrosine Aminotransferase and Tryptophan Oxygenase, at the mRNA Level

Abstract: We recently showed that annexin III is expressed in isolated small rat hepatocytes but, not in parenchymal hepatocytes. In the present study, we used reverse transcription polymerase chain analysis to examine the annexin III mRNA level in isolated small rat hepatocytes and parenchymal hepatocytes. Annexin III mRNA was detected in isolated small hepatocytes, but not in isolated parenchymal hepatocytes, confirming the presence of annexin III expression in isolated small rat hepatocytes at the mRNA level and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…15) Recently, we found that AnxA3 protein and its mRNA are not expressed in isolated parenchymal rat hepatocytes. 16,17) Consistent with these findings, AnxA3 protein and its mRNA are not detectable by Western blot analysis and Northern blot analysis in rat liver. [18][19][20][21] However, there have been no reports on the behavior of AnxA3 in primary cultured parenchymal rat hepatocytes.…”
Section: ϩsupporting
confidence: 54%
“…15) Recently, we found that AnxA3 protein and its mRNA are not expressed in isolated parenchymal rat hepatocytes. 16,17) Consistent with these findings, AnxA3 protein and its mRNA are not detectable by Western blot analysis and Northern blot analysis in rat liver. [18][19][20][21] However, there have been no reports on the behavior of AnxA3 in primary cultured parenchymal rat hepatocytes.…”
Section: ϩsupporting
confidence: 54%